2022
DOI: 10.1002/mds.29292
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and Outcomes of Late‐Onset Wilson's Disease: A National Registry‐Based Study

Abstract: Background Wilson's disease (WD) is usually diagnosed in children and young adults; limited data exist on late‐onset forms. Objective The aim was to characterize the clinical and paraclinical presentations, therapeutic management, and outcomes in patients with late‐onset WD. Methods Patients diagnosed with WD after age 40 years were identified from the French Wilson's Disease Registry (FWDR). Clinical, laboratory, and imaging findings and treatment were reported at diagnosis and last follow‐up. Results Forty‐f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 49 publications
(103 reference statements)
0
3
0
Order By: Relevance
“…In this study, WD presented mostly as hepatic symptoms (54.8%, n = 46) and less frequently neuropsychiatric (10.7%, n = 9), also consistent with previous studies where hepatic manifestations are reported in 45% [ 7 , 16 ]. As already described in the latest European Association for the Study of the Liver (EASL) guidelines on WD, hepatic manifestations are highly variable, ranging from asymptomatic to overt cirrhosis and fulminant hepatitis [ 16 ]. A liver transplant was accomplished in 23.9% (n = 21), mostly in the context of fulminant hepatitis.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In this study, WD presented mostly as hepatic symptoms (54.8%, n = 46) and less frequently neuropsychiatric (10.7%, n = 9), also consistent with previous studies where hepatic manifestations are reported in 45% [ 7 , 16 ]. As already described in the latest European Association for the Study of the Liver (EASL) guidelines on WD, hepatic manifestations are highly variable, ranging from asymptomatic to overt cirrhosis and fulminant hepatitis [ 16 ]. A liver transplant was accomplished in 23.9% (n = 21), mostly in the context of fulminant hepatitis.…”
Section: Discussionsupporting
confidence: 92%
“…A liver transplant was accomplished in 23.9% (n = 21), mostly in the context of fulminant hepatitis. The age of presentation for predominantly neurological patients is described to be between 20 and 30 years of age and mainly hepatic manifestations often present between 10 and 13 years of age [ 16 - 18 ]. Neurological patients are, therefore, diagnosed at an older age, about 10 years later in comparison with that described in other studies and an average of five years in our sample [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…The French Wilson's Disease Registry reported 8% of their cohort (45) patient were diagnosed after age 40 years (median age 49). 6 Many patients with these later diagnoses had predominantly neurologic presentations with potentially isolated long-lasting symptoms (including writer's cramp, cervical dystonia, and functional neurologic disorders-tremor and myoclonus). There was a notable absence of KF rings and MRIs were unremarkable.…”
Section: Discussionmentioning
confidence: 99%
“…It is worth noting that a neuropsychiatric presentation in Wilson's disease has previously been associated with diagnostic delays and late‐onset disease. 2 , 3 However, even in the late‐onset cases with neurological presentation, the majority of patients improve clinically with treatment. 2 While it is standard practice to consider Wilson's disease in the diagnostic evaluation of acute and chronic liver diseases, the same level of suspicion may not always extend to patients presenting with diverse neuropsychiatric symptoms without obvious liver abnormalities.…”
mentioning
confidence: 99%
“… 2 , 3 However, even in the late‐onset cases with neurological presentation, the majority of patients improve clinically with treatment. 2 While it is standard practice to consider Wilson's disease in the diagnostic evaluation of acute and chronic liver diseases, the same level of suspicion may not always extend to patients presenting with diverse neuropsychiatric symptoms without obvious liver abnormalities. This underscores the need for clear guidelines on when to suspect Wilson's disease in the diagnostic evaluation of especially adult patients presenting with neuropsychiatric symptoms.…”
mentioning
confidence: 99%